Hurricane Maria : stories from the storm [videorecording (DVD)] (Dreamscape Media, LLC, 2020)
In the aftermath of the second deadliest storm in US history, an overwhelming sense of community emerged as Puerto Ricans united to overcome Hurricane Maria.